Some solutions to develop the post-graduate lecturers at Trade Union University - Trần Thị Hoài Thu (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Developing post-graduate lecturers is an urgent task in training institutions in the era of international economic integration. Training institutions need to develop a contingent of post-graduate lecturers with sufficient quantity, quality assurance and synchronous structure, which directly affects the effectiveness, quality and training objectives. However, due to various reasons, the current post-graduate lecturers of Trade Union University is still thin, the number increases slowly, and the structure of lecturers of each training branch is still unreasonable. Therefore, the University needs to have appropriate measures and policies to develop lecturers to meet the requirements of training in general and post-graduate in particular.